Asymmetrical conversations: contestations, circumventions, and the blurring of therapeutic boundaries - Naraindas, Harish; Quack, Johannes; Sax, William Sturman (Epistemologies of Healing, 2014)
Ideas about health are reinforced by institutions and their corresponding practices, such as donning a patient's gown in a hospital or prostrating before a healing shrine. Even though we are socialized into regarding such ideologies as ""natural"" and unproblematic, we sometimes seek to bypass, circumvent, or even transcend the dominant ideologies of our cultures as they are manifested in the institutions of health care. The contributors to this volume describe such contestations and circumventions of health ideologies, and the blurring of therapeutic boundaries, on the basis of case studies